Gastric outlet obstruction due to extraluminal compression: an unusual etiology - Chatterjee, S; Basu, A (Department of Surgery, UKM Medical Centre, 2012)
Ascariasis caused by the nematode Ascaris lumbricoides is a very common disorder amongst the Asian population. Adult roundworms are generally found in the intestine. But their agility often takes them through different orifices into ducts and cavities. Hepatobiliary and pancreatic ascariasis (HPA) refers to a group of diseases caused by migration of the Ascaris from the intestine into the biliary tree and pancreatic duct through the ampulla of Vater. Depending on the position of the nematode, HPA has widespread manifestations like biliary colic, acalculous cholecystitis, obstructive jaundice, cholangitis, pancreatitis and liver abscess. Surgical interventions are rarely required as approximately 95% of the patients with uncomplicated biliary ascariasis respond to conservative management. Ultrasonography of the abdomen, CECT & ERCP all can demonstrate ascaris as linear filling defect . Here we present a case that presented with features of acute gastric outlet obstruction and obstructive jaundice as a result of extraluminal antral compression by a worm ball.